1997
DOI: 10.1038/sj.bjp.0701111
|View full text |Cite
|
Sign up to set email alerts
|

Central antitussive activity of the NK1 and NK2 tachykinin receptor antagonists, CP‐99,994 and SR 48968, in the guinea‐pig and cat

Abstract: 1 The purpose of this study was to investigate the antitussive activity and sites of action of the NK 1 and NK 2 tachykinin receptor antagonists, 994, SR 48968, and the racemate of SR 48968, SR 48212A in the cat and guinea-pig. 2 Guinea-pigs were dosed subcutaneously (s.c.) with CP-99,994, SR 48212A or SR 48968 one hour before exposure to aerosols of capsaicin (0.3 mM) to elicit coughing. Coughs were detected with a microphone and counted. 3 Intracerebroventricular (i.c.v.) cannulae were placed in the lateral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
76
3

Year Published

2000
2000
2008
2008

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(84 citation statements)
references
References 23 publications
5
76
3
Order By: Relevance
“…Several brain stem Varied results have been obtained with CP-99,994 or different NK 1 receptor antagonists in anesthetized and unanesthetized animals of different species as well as in asthmatic patients (e.g., and for further references, see Refs. 1,7,8,17,28,40 ). In particular, our results on the effects of CP-99,994 on cough are consistent with those previously described by Bolser and colleagues (7,8) and with those of a recent study by Chapman et al (17) in dogs orally dosed with this antagonist.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Several brain stem Varied results have been obtained with CP-99,994 or different NK 1 receptor antagonists in anesthetized and unanesthetized animals of different species as well as in asthmatic patients (e.g., and for further references, see Refs. 1,7,8,17,28,40 ). In particular, our results on the effects of CP-99,994 on cough are consistent with those previously described by Bolser and colleagues (7,8) and with those of a recent study by Chapman et al (17) in dogs orally dosed with this antagonist.…”
Section: Discussionsupporting
confidence: 82%
“…1,7,8,17,28,40 ). In particular, our results on the effects of CP-99,994 on cough are consistent with those previously described by Bolser and colleagues (7,8) and with those of a recent study by Chapman et al (17) in dogs orally dosed with this antagonist. On the contrary, they are at variance with those obtained by Mazzone et al (40).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Both capsaicin and citric acid are thought to act through the release of neurokinins, especially substance P, from Cfibers. Furthermore, neurokinin receptor (NK1, NK2, NK3) antagonists inhibit the cough reflex, and in guinea pigs, cats, and humans, citric acid-induced coughing is enhanced by inhibitors of two enzymes involved in substance P degradation: neutral endopeptidase and angiotensin-converting enzyme (Ujiie et al 1993;Fox et al 1996;Sekizawa et al 1996;Advenier et al 1997;Bolser et al 1997). These facts support the view that substance P plays a role in the cough reflex.…”
Section: Discussionsupporting
confidence: 55%
“…Nevertheless, pharmacologic studies have demonstrated that the NK receptors NK 1 , NK 2 , and NK 3 are present in secondary neurons within the nucleus of the solitary tract, and stimulation of these receptors can profoundly affect vagal reflex physiology (85). Also consistent with a role for tachykinins in modulating airway reflexes, the NK 1 receptor-selective antagonist CP-99,994 and SR-48968, an NK 2 receptor-selective antagonist, were able to inhibit mechanically induced cough in the guinea pig and cat by an action in the central nervous system (86).…”
Section: Enhanced Release Of Tachykininsmentioning
confidence: 85%